From techie to boss : transitioning to leadership - Cromar, Scott (Apress Imprint: Apress, 2013)
From Techie to Boss teaches technical people who are making or mulling the transition from team player to team leader all the management techniques and soft leadership skills they never needed before-but need now, pronto. Veteran team lead and project manager Scott Cromar lays out the classical management training course, but stripped down to precisely the essentials that techies need to start managing on the fly. He gets it that a front-line techie getting a field promotion to team leader just doesn't have the time to wade through an MBA textbook bulging with irrelevant material. The author appreciates how you got to the place where you need this book. Management tapped you instead of some experienced manager from the outside because you know the technical challenges, company culture, and team players better than anyone else: you're ready to hit the ground running. But the skills that make you an excellent techie are not sufficient to make you a successful manager. The rules of your world have abruptly changed. You will now be judged not by your puzzle-solving elegance but by how effectively your team contributes to the organization's bottom line.   From Techie to Boss shows you how to translate and adapt the analytic skills that made you an outstanding techie to your new responsibilities as a technical manager. Even more crucially, this book teaches you a whole new set of interpersonal, organizational, and metrical skills you never needed before, but without which you cannot succeed as a manager.